Spinal Hyper-Excitability and Altered Muscle Structure Contribute to Muscle Hypertonia in Newborns After Antenatal Hypoxia-Ischemia in a Rabbit Cerebral Palsy Model - Synowiec, Sylvia; Lu, Jing; Yu, Lei; Goussakov, Ivan; Lieber, Richard; Drobyshevsky, Alexander (Frontiers in Neurology, 2019)
Rabbit kits after global antenatal hypoxic-ischemic injury exhibit motor deficits similar to humans with cerebral palsy. We tested several mechanisms previously implicated in spinal hyper-excitability after perinatal brain injury that may explain muscle hypertonia in newborns. Stiffness of hind limb muscles during passive stretch, electromyogram, and spinal excitability by Hoffman reflex, were assessed in rabbit kits with muscle hypertonia after global hypoxic-ischemic brain injury and naïve controls. Affected muscle architecture, motoneuron morphology, primary afferents density, gliosis, and KCC2 expression transporter in the spinal cord were also examined. Decrease knee stiffness after anesthetic administration was larger, but residual stiffness was higher in hypertonic kits compared to controls. Hypertonic kits exhibited muscle shortening and atrophy, in both agonists and antagonists. Sarcomere length was longer in tibialis anterior in hypertonic kits than in controls. Hypertonic kits had decreased rate dependent depression and increased Hmax/Mmax in H-reflex. Motor neuron soma sizes, primary afferent density were not different between controls and hypertonic kits. Length of dendritic tree and ramification index were lower in hypertonic group. Gene expression of KCC2 was lower in hypertonic kits, but protein content was not different between the groups. In conclusion, while we found evidence of decreased supraspinal inhibitory control and increased excitability by H-reflex that may contribute to neuronal component in hypertonia, increased joint resistance to stretch was explained predominantly by changes in passive properties of muscles and joints. We did not find structural evidence of increased sensory afferent input or morphological changes in motoneurons that might explain increased excitability. Gliosis, observed in spinal gray matter, may contribute to muscle hypertonia.